Pengaruh Fungisida Berbahan Aktif Tunggal Mancozeb, Karbendazim, dan Campuran Terhadap Pertumbuhan Jamur Colletotrichum Gloeosporioides Secara In Vitro - MALAU, RACHEL; KHALIMI, KHAMDAN; SUDANA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.11, No.4, Oktober 2022, 2023)
Effect of Fungicides Containing Mancozeb, Carbendazim and mixture On Growth of Colletotrichum gloeosporioides In Vitro   The fungus C. gloeosporioides is the cause of anthracnose disease in onion plants. Anthracnose can cause yield losses of up to 100%. Control of anthracnose in onion plants can be done by spraying fungicides with the active ingredients of mancozeb, carbendazim, and a mixture of mancozeb and carbendazim. The purpose of this study was to test the fungicides of the active ingredients of mancozeb, carbendazim, and a mixture of mancozeb and carbendazim in inhibiting the growth of C. gloeosporoides in vitro. Fungicide testing was carried out using the Poisoned Food Technique. The results showed that fungicides with active ingredients mixed between mancozeb and carbendazim had the highest inhibition of 99.25%, followed by fungicides with active ingredients of 10% carbendazim with 99.22% inhibition, and 70% mancozeb fungicides with 75.53% inhibition.